Effect of Vitamin A on Listeria monocytogenes Infection in a Silkworm Model. - Yussaira Castillo; Jin Suzuki; Kenta Watanabe; Takashi Shimizu; Masahisa Watarai (PLoS ONE, 2016)
Insect infection models have been used increasingly to study various pathogenic agents in evaluations of pathogenicity and drug efficacy. In this study, we demonstrated that larvae of the silkworm Bombyx mori are useful for studying Listeria monocytogenes infections in insects. Infection with the L. monocytogenes wild-type strain induced silkworm death. Infection by a listeriolysin O (LLO) deletion mutant also induced silkworm death, but the bacterial numbers in silkworms were lower than those of the wild-type strain. Intracellular growth was observed when the silkworm ovary-derived cell line BmN4 was infected with the wild-type strain. Explosive replication was not observed in BmN4 cells infected with the LLO mutant and the bacterial numbers of the LLO mutant were lower than those of the wild-type strain. Pretreatment with vitamin A did not affect silkworm mortality after bacterial infection, but the efficiency of infecting the hemocytes and BmN4 cells was decreased with vitamin A treatment. Our results indicate that silkworm larvae are a useful insect infection model for L. monocytogenes and that vitamin A has protective effects against bacterial infection in silkworms.